A new model of a hydraulic leveraged dynamic anti-resonance vibration isolator under base excitation: A theoretical and experimental study. (August 2019) - Liu, Niuniu; Jin, Zeyu; Hua, Hongxing
Two models have previously been commonly used to predict the isolation performance of a hydraulic leveraged dynamic anti-resonance vibration isolator. The models have deficiencies, however, in considering the volumetric stiffness of the isolator. In this paper, a new model is proposed to improve the accuracy by reasonably taking the volumetric stiffness into consideration. The model is validated by a carefully designed experiment. The influence of the volumetric stiffness on the isolation performance of the isolator is investigated by the validated model. The results indicate that the volumetric stiffness of the isolator and its location in a mathematical model have a significant influence on the isolation frequency and the second natural frequency of the isolator. The dependence of the volumetric stiffness on the isolation frequency, the attenuation capacity at the isolation frequency, and the bandgap of the isolator is presented. The investigation will enhance the understanding of the hydraulic leveraged dynamic anti-resonance vibration isolator, and facilitate the design and exploitation of this type of isolator in the field of vibration isolation.